Predictive Analysis of The National Defense Index (IBN) on National Resilience Using Classification and Regression Trees (CART) Method - Qotrunnada, Farah Mufida; Budiyanto, Setiyo; Wadjdi, Achmad Farid (Formosa Journal of Science and Technology, 2025)
IBN (National Defense Index) is an important indicator in measuring public awareness and participation in maintaining the sovereignty and stability of the country. With the increasing complexity of challenges to national resilience, a predictive approach is needed to understand the relationship between IBN and other variables that influence national resilience. The CART method is used to identify patterns and determine significant variables that play a role in strengthening national resilience. Through this model, the study aims to provide deeper insight for the formulation of more effective policies in building strong national resilience. The results of the study were obtained by identifying factors that influence the National Defense Index (IBN). The results of this study are expected to be a consideration for the basis for strategic policies in achieving the great goal of Indonesia Emas 2045 as a strong, sovereign, and sustainable country.